Nutcracker syndrome: A case report and review of the literature - Kaur, Ramandeep; Airey, David (Frontiers in Surgery, 2022)
Background Nutcracker syndrome (NS) is an uncommon condition resulting from compression of the left renal vein between the aorta and superior mesenteric artery resulting in symptoms such as flank pain and haematuria. Case Presentation We present a case of a 30 year old woman complaining of abdominal pain who was found to have nutcracker syndrome and treated with endovascular stenting of the left renal vein. Discussion We review the literature relating to endovascular treatment of NS with focus on the distribution of the sizes of stents and rates of stent migration. Conclusion NCS is a rare condition requiring a high index of suspicion for diagnosis. Endovascular treatment is a reasonable option but it’s limitations must be considered.